Patient-reported outcome measures and prosthetic events in implant-supported mandibular overdenture patients after immediate versus delayed loading: A systematic review and meta-analysis - Ribeiro, Anne Kaline Claudino; Costa, Rayanna Thayse Florêncio; Vasconcelos, Belmiro Cavalcanti do Egito; de Moraes, Sandra Lúcia Dantas; Carreiro, Adriana da Fonte Porto; Pellizzer, Eduardo Piza [UNESP] (Elsevier, 2022)
Statement of problem: Immediately loaded mandibular overdentures are clinically acceptable treatment options that have gained popularity because their use shortens the treatment duration. However, whether the immediate loading of dental implants can match the prosthetic events, satisfaction, and quality of life of delayed loading is still unclear. Purpose: The purpose of this systematic review and meta-analysis was to compare the prosthetic events, satisfaction, and quality of life of immediate versus delayed loading implants in patients rehabilitated with mandibular overdentures. Material and methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and was registered at The International Prospective Register of Systematic Reviews (PROSPERO) (CRD42021258187). Electronic searches were carried out by 2 independent reviewers in the PubMed/MEDLINE, Cochrane Library, and Web of Science databases up to May 2021. Only randomized clinical trials and prospective studies with at least 10 participants that compared immediate versus delayed loading were selected. A meta-analysis was performed by using the RevMan 5 software program for complications and maintenance outcomes. Results: Seven articles were included in the qualitative analysis, and 4 were included in the quantitative analysis. The meta-analysis demonstrated no significant difference between immediate and delayed loading for prosthetic complications (RR=1.71; 95% CI=0.67-4.37; I2=85%, P=.27) or maintenance (RR=1.92, 95% CI=0.44-8.28; I2=94%, P=.38). Conclusions: Although the prosthetic complications and maintenance were more likely to favor the delayed loading group, available evidence showed no statistical difference for prosthetic complications and maintenance between immediate loading and delayed loading in mandibular overdentures.